Transnational Railway Cultures : Trains in Music, Literature, Film, and Visual Art. - Fraser, Benjamin (Berghahn Books, Incorporated, 2021)
Since the advent of train travel, railways have compressed space and crossed national boundaries to become transnational icons, evoking hope, dread, progress, or obsolescence in different cultural domains. Spanning five continents and a diverse range of contexts, this collection offers an unprecedentedly broad survey of global representations of trains. From experimental novels to Hollywood blockbusters, the works studied here chart fascinating routes across a remarkably varied cultural landscape.
Description based upon print version of record.
Keywords: Railroad travel -- Social aspects.; Railroads -- Social aspects.; Railroad travel in popular culture.; Voyages en train -- Aspect social.; TRANSPORTATION / Railroads / General.; Railroads -- Social aspects